Fundamentals of puzzle and casual game design - Adams, Ernest (Ernest W.) (New Riders, 2014)
You understand the basic concepts of game design: gameplay, user interfaces, core mechanics, character design, and storytelling. Now you want to know how to apply them to the puzzle and casual game genres. This focused guide gives you exactly what you need. It walks you through the process of designing for the puzzle and casual game genres and shows you how to use the right techniques to create fun and challenging experiences for your players.